Teaching mathematics online : emergent technologies and methodologies - Juan, Angel A., 1972- (Hershey, P.A. : Information Science Reference, 2012)
"This book shares theoretical and applied pedagogical models and systems used in math e-learning including the use of computer supported collaborative learning, which is common to most e-learning practices"--